2021
DOI: 10.3390/antiox10121902
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Redox State of Human Peroxiredoxin-5 on Its TLR4-Activating DAMP Function

Abstract: Human peroxiredoxin-5 (PRDX5) is a unique redox-sensitive protein that plays a dual role in brain ischemia-reperfusion injury. While intracellular PRDX5 has been reported to act as a neuroprotective antioxidative enzyme by scavenging peroxides, once released extracellularly from necrotic brain cells, the protein aggravates neural cell death by inducing expression of proinflammatory cytokines in macrophages through activation of Toll-like receptor (TLR) 2 (TLR2) and 4 (TLR4). Although recent evidence showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…The authors validated this proteomic data set by performing Western blots on independent samples of tissue and exosomes in the CRSwNP and HS groups and confirmed that CST-1, PRDX5, and GP6 were significantly differentially expressed in both tissue and exosomes among the CRSwNP group relative to HS group [ 15 ]. Peroxiredoxin-5 (PRDX5) might trigger a proinflammatory response by inducing the expression of proinflammatory cytokines in macrophages through activation of Toll-like receptors [ 111 , 112 ]. The activation of toll-like receptor 4 (TLR4) is important for initiating allergic inflammation and antifungal immunity [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors validated this proteomic data set by performing Western blots on independent samples of tissue and exosomes in the CRSwNP and HS groups and confirmed that CST-1, PRDX5, and GP6 were significantly differentially expressed in both tissue and exosomes among the CRSwNP group relative to HS group [ 15 ]. Peroxiredoxin-5 (PRDX5) might trigger a proinflammatory response by inducing the expression of proinflammatory cytokines in macrophages through activation of Toll-like receptors [ 111 , 112 ]. The activation of toll-like receptor 4 (TLR4) is important for initiating allergic inflammation and antifungal immunity [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…41 PRDX5, involved in redox balance during brain ischemia-reperfusion, presents a dual role; intracellularly exerting neuroprotective effects and extracellularly inducing pro-inflammatory responses. 42 In conclusion, CD14, GPNMB, SPP1, PRDX5 and macrophages stand central in orchestrating inflammatory responses, tissue repair and neuroprotection in SAH. Further exploration of their interaction mechanisms, regulatory roles in macrophage activation and crosstalk with signalling pathways will deepen our understanding of SAH pathogenesis, paving the way for innovative therapeutic strategies.…”
Section: Discussionmentioning
confidence: 96%
“…Its neuroprotective effects, counterbalanced by potential contributions to chronic hydrocephalus underscore the need for nuanced investigations 41 . PRDX5, involved in redox balance during brain ischemia–reperfusion, presents a dual role; intracellularly exerting neuroprotective effects and extracellularly inducing pro‐inflammatory responses 42 …”
Section: Discussionmentioning
confidence: 99%
“…The AKR7A2 protein detoxifies aldehydes and ketones and catalyzes the reduction of xenobiotics ( Barski et al, 2008 ) and is increased by ZEN exposure in both TN groups but decreased in HS gilt ovaries. Similar to PRDX4 which was altered in TN gilts exposed to ZEN, PRDX5 responds to oxidative stress and induces proinflammatory cytokines in macrophages through activation of toll-like receptor 4 ( Poncin et al, 2021 ). Both TN and PF had reduced levels of PRDX5 while HS gilts had higher PRDX5 in response to ZEN.…”
Section: Discussionmentioning
confidence: 99%